Malaysian ICU nurses’ constructive response to critical ill patients transition/ experience: Qualitative analysis - Mohamed Ludin, Salizar; Parker, Steve; Arbon, Paul (2013)
Background: Providing support for critically ill patients throughout their transition(s) while in the Intensive Care Unit and following transfer is an important element of the nursing process during hospitalisation for critical illness. Because nurses are the primary caregivers in critical care contexts, nurses’ response to transition experience is important and can facilitate better nursing care. To date, apart from the associated discussion of discharge planning issues, little is known about nurses’ response to the critically ill patients and their families’ experience of transition.